Empathy influences how listeners interpret intonation and meaning when words are ambiguous. - Esteve-Gibert, Núria; Schafer, Amy J.; Hemforth, Barbara; Portes, Cristel; Pozniak, Céline; D'Imperio, Mariapaola (Memory & Cognition, 2020)
This study examines how individual pragmatic skills, and more specifically, empathy, influences language processing when a temporary lexical ambiguity can be resolved via intonation. We designed a visual-world eye-tracking experiment in which participants could anticipate a referent before disambiguating lexical information became available, by inferring either a contrast meaning or a confirmatory meaning from the intonation contour alone. Our results show that individual empathy skills determine how listeners deal with the meaning alternatives of an ambiguous referent, and the way they use intonational meaning to disambiguate the referent. Listeners with better pragmatic skills (higher empathy) were sensitive to intonation cues when forming sound–meaning associations during the unfolding of an ambiguous referent, and showed higher sensitivity to all the alternative interpretations of that ambiguous referent. Less pragmatically skilled listeners showed weaker processing of intonational meaning because they needed subsequent disambiguating material to select a referent and showed less sensitivity to the set of alternative interpretations. Overall, our results call for taking into account individual pragmatic differences in the study of intonational meaning processing and sentence comprehension in general.